Using 1D Thermal Modeling to Evaluate Formation Models of Mafic-Ultramafic Intrusions and Associated Sulfide Cu-Ni-PGE Mineralization - Dmitry Stepenshchikov; Nikolay Groshev (Minerals, 2023)
In this paper, we trace the thermal history of the mafic–ultramafic intrusions of the Monchegorsk (MC), Fedorova–Pana (FPC), and Norilsk ore-bearing complexes (NC) using an upgraded version of the author’s software Gehenna 2.2. It is shown that a key role in the concentration of sulfides in the lower parts of the intrusions belongs to the preliminary heating of the host rocks by early magmatic influxes. In the presence of late ore-bearing magmatic phases of a relatively small volume, the pattern of sulfide distribution within such a phase can be used to estimate the time gap with the main influx. Thermal modeling shows that the Gabbro-10 massif, an additional ore-bearing phase of the Nyud-Poaz intrusion of the MC, is separated from the main influx by a time gap of no more than 100 ka, while the minimum gap between the magmatic phases of the Fedorova intrusion of the FPC is 650–700 ka. The development of a hornfels halo around mafic–ultramafic rocks makes it possible to estimate the duration of the process of continuous magma flow inside intrusions, which, as an example from the Kharaelakh intrusion of the NC shows, can reach 1000 years and more. Thermal modeling is recommended both for formulating genetic hypotheses and for testing different scenarios for the formation of sulfide Cu-Ni-PGE mineralization in mafic–ultramafic complexes.